E-Commerce or Traditional Purchasing Channel: Segmenting The Agro-Food Consumers in Cross River State, Nigeria - Amarachi E. Uzoigwe; Susanna B. Ohen (Journal of Global Innovations in Agricultural Sciences)
Agro-food sector in Nigeria has witnessed a paradigm shift in the mode of commercial activities from traditional purchase channel to E-commerce purchase channel. However, studies show that a good number of consumers insist on the traditional purchase channel for agro-food purchase. Hence, to enable effective policy recommendations, this study was designed to identify consumer’s choice of purchase channel for various agro-food products as well as identify distinct channel segments of the agro-food market in Cross-River State, Nigeria. To achieve this, a two-stage sampling technique was employed to select a total of 352 agro-food consumers for the study and primary data obtained were analyzed using both descriptive and inferential statistics. The latent cluster analysis and binomial test statistics were inferential statistical tools employed in identifying distinct channel segments as well as testing the statistical significance of consumers choice of purchasing channel respectively. Results obtained showed that the respondents were predominantly female (82.6%) with ages ranging from 31-40 years and had obtained some forms of formal education. The study further recorded high preference for traditional channels in all agro-food product categories (cereals & beverages-79.1%; fruits & vegetables-92.5%; grains & flour-79.17%; oil-55.67%; tubers-85.83% and meat-93.33%). However, 30.19% of the respondents indicated preference for the use of M-commerce, showing that M-commerce has gained a wider acceptance rate than web-based purchase channels for some categories of agro-food products such as oil, cereals and beverages, grains and flour. Based on the latent class cluster analysis result, the agro-food consumers were grouped into 4 channel segments: indifferent channel buyers who are unconcerned about the purchasing channel (20.7%), loyal traditional channel buyers who are allegiant to traditional channels (10%), convenient channel buyers who are drawn by ease of access (57.5%) and service-based channel buyers who are allured by good customer service (11.9%). The study therefore recommends the use of Omni-channel (a combination of traditional and e-commerce channels) by firms and marketers for better competitive advantage and in cooperating agro-food products with longer shelf life such as oil, grains and flour in a firm’s E-commerce product line. Keywords: E-commerce, Purchasing Channels, M-commerce, Market segmentation, Agro-food.